Marvellous Magical Stories - Compiled by Elizabeth Holland and Illustrated by Sarah Horne (London Kingfisher, 2007)
Short Stories. A new series of themed short story collections, Super Shorts are sure to appeal to newly confident readers. These short, well-plotted, easy-to-read stories are written by popular authors. The generous layout, with fun, modern illustrations on every spread, encourages readers to make progress towards tackling longer fiction.
Including Pictures
Keywords: Magic -- Short stories, English -- Children's stories, English